Improving mobile learning in secondary mathematics and science: Listening to students - Burke, Paul F.; Kearney, Matthew; Schuck, Sandy; Aubusson, Peter (Journal of computer assisted learning, 2022)
Background Mobile learning studies often focus on teachers' perspectives. This study instead considers students' experiences of learning with mobile devices (i.e., m‐learning) in secondary school mathematics and science. Objectives The research aims to describe the m‐learning experiences of secondary mathematics and science students, and to determine the extent to which distinctive pedagogical dimensions impact students' perceived learning. Methods A survey instrument using the iPAC mobile pedagogical framework as a theoretical lens is developed and validated. This framework highlights three pedagogical dimensions: personalization, authenticity, and collaboration. Structural equation modelling is used to investigate how each dimension predicts students' perceived improvement in learning, whilst accounting for usage context, among a sample of students in schools where mobile devices are used extensively. Results and Conclusions Students were in agreement that personalization was a characteristic of their m‐learning experiences, but authentic and collaborative learning were not as strongly featured. M‐learning activities fostering personalization were most important for improving perceived learning; authenticity and collaboration were also significant, but no differences in perceived learning improvement due to location were found. Authentic m‐learning and perceived improvement in learning with mobile devices were significantly higher in science than mathematics subjects. Implications When teachers design m‐learning tasks that enhance personalization, collaboration, and authenticity, students are predicted to perceive improvements in their learning. The findings suggest that teachers should consider designing technology‐enhanced tasks that improve students' experiences of collaborative and authentic learning, particularly in mathematics for greatest gains in students' perceived improvement in learning. Lay Description What is already known about this topic: Mobile learning studies often focus on teachers' perspectives and practices or expert commentaries. Issues of usability, access, engagement, motivation, and potential risk are often highlighted rather than pedagogical factors. Mobile technologies provide students with opportunities for more personalized and autonomous seamless experiences across learning contexts. Science teachers frequently use authentic and project‐based m‐learning opportunities, whilst mathematics teachers prefer didactic, drill and practice approaches. What this paper adds: This study focuses on students' m‐learning in secondary mathematics and science. A multi‐item scale considering aspects of authenticity, personalization, collaboration and context is developed and validated. Personalization in m‐learning activities are most important for perceived learning, followed by authenticity and collaboration. Science students report greater authenticity and perceived learning in m‐learning than mathematics students. Implications for practice and/or policy: Highlighting the student perspective is a valued lens to evaluate m‐learning pedagogy and outcomes in student learning. Efforts should be made to develop mobile pedagogies, particularly with respect to authenticity and collaboration. Teachers in mathematics would benefit most from examining practices that improve authenticity.